2008
DOI: 10.1093/carcin/bgn078
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin, a novel dietary flavonoid, causes apoptosis and cell cycle arrest in human prostate cancer LNCaP cells

Abstract: Novel dietary agents for prevention and therapy of prostate cancer (PCa) are desired. The aim of this study was to determine the effect of fisetin, a tetrahydroxyflavone, on inhibition of cell growth and induction of apoptosis in human PCa cells. Treatment of fisetin (10-60 microM, 48 h) was found to result in a decrease in the viability of LNCaP, CWR22Rupsilon1 and PC-3 cells but had only minimal effects on normal prostate epithelial cells as assessed by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazoliumbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
166
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(179 citation statements)
references
References 32 publications
13
166
0
Order By: Relevance
“…Numerous reports have shown that fisetin induced cytotoxic effects on many human cancer cell lines through cell-cycle arrest and apoptosis (20,(22)(23)(24)(25)(26)(27)(28)(29), however, there is no report demonstrating that fisetin induces apoptosis of human oral cancer cells, therefore, we investigated the cytotoxic effects of fisetin on HSC3 human oral cancer cells in vitro. It is well documented that the best strategy for anticancer drugs is to induce cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports have shown that fisetin induced cytotoxic effects on many human cancer cell lines through cell-cycle arrest and apoptosis (20,(22)(23)(24)(25)(26)(27)(28)(29), however, there is no report demonstrating that fisetin induces apoptosis of human oral cancer cells, therefore, we investigated the cytotoxic effects of fisetin on HSC3 human oral cancer cells in vitro. It is well documented that the best strategy for anticancer drugs is to induce cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Fisetin (3,7,3',4'-tetrahydroxyflavone), a naturally-occurring flavonoid, is widely distributed among edible vegetables and fruits such as apple, cucumber, grapes, kiwis, onion, persimmon and strawberry, the highest level of fisetin (160 μg/g wet food) being found in strawberries (14). Numerous studies have shown that fisetin has pharmacological activities such as antioxidant (15), anti-inflammatory (16), anti-invasive (17,18), anti-angiogenesis (19,20), anti-proliferation (21,22) and anticancer effects in several cancer types, such as prostate cancer (22,23), lung adenocarcinoma (20,24), pancreatic cancer (25), colon cancer (26), cervical cancer (27), melanoma (28) and acute monocytic leukemia cells (29). Recently, it was reported that combination treatment of fisetin and sorafenib effectively inhibited B-Raf proto-oncogene serine/threonine-protein kinase (BRAF)-mutated melanoma cell growth, induced apoptosis, and down-regulated mitogenactivated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K) signaling pathways in vitro and in vivo.…”
mentioning
confidence: 99%
“…For instance, in LNCaP prostate cancer cells, fisetinmediated apoptosis was related to activation of caspase cascade [19]. In a recent study, Kang et al [20] displayed that fisetin had a dose-dependent cytotoxic effect on NCI-H460 human non-small cell lung cancer cells, and apoptosis induction in these cells was related to mitochondrial membrane depolarization and caspase-3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture studies show that fisetin exerts antiproliferative effect on human CaP cells. Data from our laboratory indicate that fisetin selectively decreases the viability of LNCaP, CWR22Rν1 and PC-3 CaP but has only minimal effect on normal prostate epithelial cells [44]. Flowcytometric analysis indicated that the cell cycle arrest observed in PC3 cells was in G2/M phase whereas the LNCaP cells demonstrated a different cell cycle profile [45].…”
Section: Fisetinmentioning
confidence: 91%
“…Fisetin can be found in many fruits such as strawberries, apple, persimmon, kiwi fruit and vegetables including onion and cucumber [44]. Cell culture studies show that fisetin exerts antiproliferative effect on human CaP cells.…”
Section: Fisetinmentioning
confidence: 99%